Guidelines of the International Headache Society for controlled trials of acute treatment of migraine attacks in adults: Fourth edition. (May 2019) - Diener, Hans-Christoph; Tassorelli, Cristina; Dodick, David W; Silberstein, Stephen D; Lipton, Richard B; Ashina, Messoud; Becker, Werner J; Ferrari, Michel D; Goadsby, Peter J; Pozo-Rosich, Patricia; Wang, Shuu-Jiun; Mandrekar, Jay; et al.
The quality of clinical trials is an essential part of the evidence base for the treatment of headache disorders. In 1991, the International Headache Society Clinical Trials Standing Committee developed and published the first edition of the Guidelines for controlled trials of drugs in migraine . Scientific and clinical developments in headache medicine led to second and third editions in 2000 and 2012, respectively. The current, fourth edition of the Guidelines retains the structure and much content from previous editions. However, it also incorporates evidence from clinical trials published after the third edition as well as feedback from meetings with regulators, pharmaceutical and device manufacturers, and patient associations. Its final form reflects the collective expertise and judgement of the Committee. These updated recommendations and commentary are intended to meet the Society's continuing objective of providing a contemporary, standardized, and evidence-based approach to the conduct and reporting of randomised controlled trials for the acute treatment of migraine attacks.